Influence of Properties of Hydraulic Fluid on Pressure Peaks in Axial Piston Pumps’ Chambers - Piotr Patrosz (Energies, 2021)
The article concentrates on the research of the pressure peaks in a working chamber of an axial piston pump. The main focus of the article is the influence of fluid properties on the pressure peaks value. Experimental and analytical methods were used to determine the impact of the fluid density, viscosity, compressibility and aeration. The article describes the pressure peak generation process and explains the theoretical basis of this phenomenon. A model of aerated fluid compression and models of leakage were created using CFD analysis and mathematical equations. These partial models were then merged into one consistent model in Matlab Simulink. The final result was verified by comparing the results obtained from the mathematical model with the results of the experiment. After validation, the model was used to present explicitly how each of the mentioned fluid properties affects the pressure peak value. Additionally, the test stand and measurement equipment used in the experiment were presented along with a short description of the laboratory research and sample results.